ANALISIS TINGKAT KEUNTUNGAN USAHA RUMAH TANGGA KUE LUMPIA DI KELURAHAN BUMI NYIUR KECAMATAN WANEA - Novel Novri Sumampouw; O. Esry Laoh; Lyndon R.J. Pangemanan (Sam Ratulangi University, 2015)
The objective of this research is to to determine the level of profit from the Cake Lumpia households business in the Bumi Nyiur Village Wanea districts. The method used in this study is the case study method. The data used in this study are primary data and secondary data. Primary data were collected in the field directly from the source in this research is the owner of household enterprises cakes spring rolls, for the purpose of research and the data has not been published before. This data was obtained through interviews based on questionnaires that are relevant and have been prepared. As for the secondary data includes vil-lage profiles will be obtained from government agencies associated with this research. To determine the amount of benefit artisans will use a rat stamp benefit analysis followed by analysis of R / C to determine the feasibility of this venture. These results indicate that the average total revenue in this business is Rp. 1,000,000 / day, with a total production cost of Rp. 283,896.7. Then the total profit earned in spring roll pastry business in Bumi Nyiur Village, District of Wanea is Rp. 716,103.3 / day. Analysis of R / C who do show that the average household businesses spring rolls baking in the Village Earth Nyiur District of Wanea experiencing gains, where the R / C ratio of 3.52 and it can be concluded that the business is feasible to run.